Habit Formation, Dynastic Altruism, and Population Dynamics - Andreas Schäfer; Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
We study the general equilibrium properties of two growth models with overlapping generations, habit formation and endogenous fertility. In the neoclassical model, habits modify the economy's growth rate and generate transitional dynamics in fertility; station- ary income per capita is associated with either increasing or decreasing population and output, depending on the strength of habits. In the AK specification, growing population and increasing consumption per capita require that the habit coefficient lie within definite boundaries; outside the critical interval, positive growth is associated with either declining consumption due to overcrowding, or extinction paths with declining population. In both frameworks, habits reduce fertility: the trade-off between second-period consumption and spending for bequests prompts agents to decrease fertility in order to make parental altru- ism less costly. This mechanism suggests that status-dependent preferences may explain part of the decline in fertility rates observed in most developed economies.
Keywords: D91; J10; O11; 330; Economic Growth; Endogenous Fertility; Habit Formation; Intergenerational Altruism; Overlapping Generations; Wirtschaftswachstum; Generationengerechtigkeit; Altruismus; Soziale Werte; Fertilität; Konsumentenverhalten; Overlapping Generations; Neoklassische Theorie; Wachstumstheorie; Theorie